Tersilochinae of Western Amazonia (Hymenoptera: Ichneumonidae). Genus Stethantyx Townes, part 1 - Khalaim, Andrey I.; Sääksjärvi, Ilari E.; Bordera, Santiago (Zootaxa, 2013)
Sixteen species of the genus Stethantyx Townes having first and second sections of radius meeting at obtuse angle are recorded from Peru and Ecuador in Western Amazonia. Ten species, S. amazonica Khalaim & Sääksjärvi, sp. nov., S. aurantia Khalaim & Sääksjärvi, sp. nov., S. juninensis Khalaim & Bordera, sp. nov., S. loretosa Khalaim & Sääksjärvi, sp. nov., S. neopropodeator Khalaim & Sääksjärvi, sp. nov., S. orellana Khalaim & Sääksjärvi, sp. nov., S. sinuata Khalaim & Sääksjärvi, sp. nov., S. tiputinia Khalaim & Sääksjärvi, sp. nov., S. trepida Khalaim & Sääksjärvi, sp. nov. and S. voluptaria Khalaim & Sääksjärvi, sp. nov., are described as new. Six species, previously known only from Costa Rica,           S. alajuela Khalaim & Broad, S. heredia Khalaim & Broad, S. orosia Khalaim & Broad, S. propodeator Khalaim & Broad, S. puntarenasa Khalaim & Broad and S. sanjosea Khalaim & Broad, are recorded from South America for the first time. A partial key to Western Amazonian species of Stethantyx is given.